2013
DOI: 10.1093/ejcts/ezt252
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the conventional and frozen elephant trunk techniques: a single-centre study

Abstract: The FET procedure for extensive thoracic aortic disease is associated with an acceptable mortality rate, but with a higher incidence of perioperative spinal cord injury than cET. Arch replacement with a cET technique should be strongly considered in patients with expected prolonged circulatory arrest times, particularly if operated on under mild or moderate hypothermia. Axillary cannulation is associated with superior neurological outcomes and Type A acute aortic dissection is a risk factor for mortality and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
5
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 22 publications
8
79
5
4
Order By: Relevance
“…The literature search identified 1,268 records, of which nine satisfied the inclusion criteria and definitions for hybrid versus traditional aortic arch surgery (6,7,(18)(19)(20)(28)(29)(30)(31) (study details in Table S1). Two studies were identified as high quality, three as intermediate quality and four as standard quality using the adapted scoring criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 1,268 records, of which nine satisfied the inclusion criteria and definitions for hybrid versus traditional aortic arch surgery (6,7,(18)(19)(20)(28)(29)(30)(31) (study details in Table S1). Two studies were identified as high quality, three as intermediate quality and four as standard quality using the adapted scoring criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a hybrid total arch and frozen elephant trunk procedure has consistently been reported to incur a greater risk of spinal cord ischemia. 21 Therefore, the invasive nature of surgery does add non-negligible risks particularly to those with premorbid risk factors. Consequently, opting for the medical therapy-first strategy in patients who may benefit by an initial conservative approach should be further investigated through larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of cerebrospinal fluid drainage, adjusting the distal landing zone above the level of T7, keeping the anterograde perfusion time short, paying attention to the continuity of left subclavian artery are the precautions that can be taken for spinal cord protection. However, in spite of the protection methods of spinal cord, percentages of paraplegia as 21.7 and 24 14,20 stated in the literature are demoralizing, the presence of successful series stated as 8% and 9% 13,21 is encouraging.…”
Section: -13mentioning
confidence: 95%
“…Mortality varied between 3.8% and 17.2% in conducted studies using FET technique without grouping complex aortic diseases. 8,10,14,15,16 When the complex thoracic aortic diseases were arranged into groups, especially in type I aortic dissection, Pochettino and coworkers 9 stated the conditions requiring emergency cardiac surgery as an independent risk factor for mortality and it was reported that mortality percentage was 13.9 for first 30 days. Likewise, as known, acute type I aortic dissection with mortality percentage varying between 7.8 and 18.2 in the literature was observed to be a predictive factor on mortality independently of operation.…”
Section: -13mentioning
confidence: 99%